Genetic variation at hair length candidate genes in elephants and the extinct woolly mammoth - Tisdale Michele; Hensley Shannon; Stewardson Kristin; Fratpietro Stephen; Kolokotronis Sergios-Orestis; Nikolaidis Nikolas; Ishida Yasuko; Roca Alfred L; Boeskorov Gennady; Greenwood Alex D (BMC Evolutionary Biology, 2009)
Abstract Background Like humans, the living elephants are unusual among mammals in being sparsely covered with hair. Relative to extant elephants, the extinct woolly mammoth, Mammuthus primigenius , had a dense hair cover and extremely long hair, which likely were adaptations to its subarctic habitat. The fibroblast growth factor 5 ( FGF5 ) gene affects hair length in a diverse set of mammalian species. Mutations in FGF5 lead to recessive long hair phenotypes in mice, dogs, and cats; and the gene has been implicated in hair length variation in rabbits. Thus, FGF5 represents a leading candidate gene for the phenotypic differences in hair length notable between extant elephants and the woolly mammoth. We therefore sequenced the three exons (except for the 3' UTR) and a portion of the promoter of FGF5 from the living elephantid species (Asian, African savanna and African forest elephants) and, using protocols for ancient DNA, from a woolly mammoth. Results Between the extant elephants and the mammoth, two single base substitutions were observed in FGF5 , neither of which alters the amino acid sequence. Modeling of the protein structure suggests that the elephantid proteins fold similarly to the human FGF5 protein. Bioinformatics analyses and DNA sequencing of another locus that has been implicated in hair cover in humans, type I hair keratin pseudogene ( KRTHAP1 ), also yielded negative results. Interestingly, KRTHAP1 is a pseudogene in elephantids as in humans (although fully functional in non-human primates). Conclusion The data suggest that the coding sequence of the FGF5 gene is not the critical determinant of hair length differences among elephantids. The results are discussed in the context of hairlessness among mammals and in terms of the potential impact of large body size, subarctic conditions, and an aquatic ancestor on hair cover in the Proboscidea.